Garlic bulb studies: Effect of day length, temperature during growth, and storage temperature on Early and Late varieties - L Mann (California Agriculture, 1952)
Garlic is one of the oldest cultivated crops—and California produces some 80% of all that is grown in the United States—but there have been few studies on its development under field conditions.